Por um estatuto epistemológico da análise do discurso (Revista de Estudos da Linguagem, 1999)
This article aims to bring some contributions to the discussion ofthe epistemological status of French Discourse Analysis. Becausethere isn’t a single answer to this question yet, this work will studyseveral authors and their observations about the French DiscourseAnalysis and its epistemologicals limits.